Behavioural finance for private banking - Hens, Thorsten (John Wiley & Sons, 2008)
A complete framework for applications of behavioral finance in private banking, Behavioural Finance for Private Banking considers client needs specific to private banking like personal circumstances, objectives, and attitude to risk. This book includes the theoretical foundations of investment decision-making, an introduction to behavioral biases, an explanation of cultural differences in global business, a guide to asset allocation over the life cycle of the investment, and several case studies to illustrate how can be applied. A must-read for anyone in private banking, this book demonstrates how to satisfy client needs.